1997
DOI: 10.1364/ao.36.008275
|View full text |Cite
|
Sign up to set email alerts
|

Reflective surfaces for panoramic imaging

Abstract: A family of reflective surfaces is presented that, when imaged by a camera, can capture a global view of the visual environment. By using these surfaces in conjunction with conventional imaging devices, it is possible to produce fields of view in excess of 180 degrees that are not affected by the distortions and aberrations found in refractive wide-angle imaging devices. By solving a differential equation expressing the camera viewing angle as a function of the angle of incidence on a reflective surface, a fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 4 publications
0
123
0
Order By: Relevance
“…Ollis et al showed how to compute mirror surfaces that provide an equiangular catadioptric sensor [386]. Previously, Chahl and Srinivasan obtained a similar result, a mirror shape where the angle between the optical axis and a ray back-projected from the camera, is proportional to the same angle after reflecting the ray in the mirror [84]. Conroy and Moore achieved a sensor with solid angle pixel density invariance, i.e., where the surface area of a circular image portion is proportional to the solid angle of the corresponding field of view [99].…”
Section: Non-central Catadioptric Camerasmentioning
confidence: 99%
“…Ollis et al showed how to compute mirror surfaces that provide an equiangular catadioptric sensor [386]. Previously, Chahl and Srinivasan obtained a similar result, a mirror shape where the angle between the optical axis and a ray back-projected from the camera, is proportional to the same angle after reflecting the ray in the mirror [84]. Conroy and Moore achieved a sensor with solid angle pixel density invariance, i.e., where the surface area of a circular image portion is proportional to the solid angle of the corresponding field of view [99].…”
Section: Non-central Catadioptric Camerasmentioning
confidence: 99%
“…We moved a panoramic imaging device (Chahl and Srinivasan 1997) along the previously recorded flight paths with the aid of the robotic gantry (Zeil et al 2003). The robotic gantry was levelled and positioned at the same place on different days by using the embedded nails as fixed external markers.…”
Section: Reconstructing Natural Optic Flowmentioning
confidence: 99%
“…The recording site is indicated by an arrow grabber and stored directly on the hard disk of a computer. These sequences were transformed (''unwarped'') offline from polar to Cartesian coordinates (Chahl et al 1997) and processed by 3-D rendering software (Open Inventor, Silicon Graphics) to interface with the data format required by the replay screen (see below). Since the panoramic imaging device cannot be rotated, the resulting image sequences contained only the translational optic flow component.…”
Section: Reconstructing Natural Optic Flowmentioning
confidence: 99%
“…The panoramic imaging device consisted of a black and white video camera (Samsung BW-410CA) looking down onto a parabolic mirror which was optimised for constant spatial resolution (Chahl and Srinivasan, 1997). In the captured images the azimuth and elevation are represented in polar coordinates, as angular position and distance from the origin in the image centre, respectively (see figure 1A).…”
Section: A B D Cmentioning
confidence: 99%